Impact of the COVID-19 pandemic on the mental state of Polish students - Florek, Szymon; Meca, Kamila; Czogalik, Łukasz; Piegza, Magdalena; Dębski, Paweł; Pudlo, Robert (Current Problems of Psychiatry, 2025)
Introduction: The COVID-19 pandemic has undoubtedly affected the mental health of the population. This issue has become the focus of interest of various research groups in recent years, resulting in a number of publications on the subject. Among other things, increases in anxiety, aggression, depression and other variables have been observed in different populations.Material and method: The authors of the present project conducted a web-based survey among university students in Poland. They used scales to assess the intensity of anxiety (GAD-7), aggressive behaviour (Buss-Perry Aggression Questionnaire -ABPQ), alcohol consumption (AUDIT test), and mental toughness (ER-89). The entire survey was conducted in two stages, with the second stage taking place by sending survey forms to email addresses previously provided by respondents.Results: In the first term of the study, higher levels of anxiety and anger and lower levels of alcohol consumption were observed among women compared to men. Medical students reported lower levels of verbal, physical and generalised aggression compared to non-medical students. A follow-up study conducted after three months showed a reduction in anxiety among students.Discussion: Adaptation to the COVID-19 pandemic among students did not differ from changes in other communities. Women are characterized by higher levels of anxiety and anger and less alcohol consumption compared to men. A significant decrease in anxiety intensity was observed in the follow-up study. Medical students were characterized by lower levels of verbal, physical and generalized aggression.